Let

f

is complete. Then take

G

(

α

) =

[ n

b

atoms 1

F

(Dst

f

)

|

Src

f

{

α

} ×

RLD

b

f

o

and we have (12) obviously.

Let (12) holds. Then

G

(

α

) =

S

atoms

G

(

α

) and thus

f

=

Src

f

{

α

} ×

RLD

b

|

α

Src

f, b

atoms

G

(

α

)

and so

f

is complete.

Obvious 24.

Complete and co-complete reloids are convex.

Obvious 25.

Principal reloids are complete and co-complete.

Obvious 26.

Join (on the lattice of reloids) of complete reloids is complete.

Corollary 14

Compl

RLD

(with the induced order) is a complete lattice.

Theorem 56

A reloid which is both complete and co-complete is principal.

Proof

Let

f

is a complete and co-complete reloid. We have

f

=

Src

f

{

α

} ×

RLD

G

(

α

)

|

α

Src

f

and

f

=

H

(

β

)

×

RLD

Dst

f

{

β

}

|

β

Dst

f

for some functions

G

: Src

f

F

(Dst

f

),

H

: Dst

f

F

(Src

f

). For every

α

Src

f

we have

G

(

α

)

=

im

f

|

Src

f

{

α

}

=

im

f

Src

f

{

α

} ×

RLD

1

F

(Dst

f

)

= (*)

im

[ n

H

(

β

)

×

RLD

Dst

f

{

β

}

Src

f

{

α

} ×

RLD

1

F

(Dst

f

)

|

β

Dst

f

o

=

im

H

(

β

)

∩ ↑

Src

f

{

α

}

×

RLD

Dst

f

{

β

}

|

β

Dst

f

=

im

[

Src

f

{

α

} ×

RLD

Dst

f

{

β

}

if

H

(

β

)

6≍↑

Src

f

{

α

}

0

RLD

(Src

f

;Dst

f

)

if

H

(

β

)

≍↑

Src

f

{

α

}

|

β

Dst

f

=

im

Src

f

{

α

} ×

RLD

Dst

f

{

β

}

|

β

Dst

f, H

(

β

)

6≍↑

Src

f

{

α

}

=

im

[ n

RLD

(Src

f

;Dst

f

)

{

(

α

;

β

)

}

|

β

Dst

f, H

(

β

)

6≍↑

Src

f

{

α

}

o

=

Dst

f

{

β

}

|

β

Dst

f, H

(

β

)

6≍↑

Src

f

{

α

}

.

* the theorem 40 from [15] was used.

Thus

G

(

α

) is a principal f.o. that is

G

(

α

) =

Dst

f

g

(

α

) for some

g

: Src

f

Dst

f

;

Src

f

{

α

} ×

RLD

G

(

α

) =

RLD

(Src

f

;Dst

f

)

(

{

α

} ×

g

(

α

));

f

is principal as a

join of principal reloids.

48